Theology and Disability: Changing the Conversation - Reynolds, Thomas E. (Journal of religion, disability & health, 2012)
This article suggests that faith communities need to change the way disability is conceived and talked about in order to more fulsomely welcome people with disabilities as participants in community life. Speaking from the context of parenting a child with disabilities, the author indicates ways the conversation needs to move beyond depicting disability as a bodily deprivation or problem to be cured or done away with, beyond the able-disabled binary that pits a normal “inside” against an “outside” in need of normalization, and beyond mere inclusive “accommodation” to disability as an access issue. As the conversation shifts, disability might become received as a matter of human difference rather than deviance, and accordingly, received as gift, one that disrupts and preempts easy closures, but in the end opens new transformative possibilities for being vulnerably human together in mutual relation.